Reduced-dose obinutuzumab induces remission in refractory ANCA-associated vasculitis: a report of 16 cases - Wu, Wenyi; Wang, Juan; Chen, Sheng (Frontiers in Immunology, 2025)
ObjectiveRituximab remains the standard-of-care anti-CD20 therapy for anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). Obinutuzumab, a next-generation, glycoengineered anti-CD20 monoclonal antibody with enhanced B-cell-depleting capacity, may offer superior efficacy. We evaluated the efficacy and safety of reduced-dose obinutuzumab in 16 patients with active, refractory AAV at a single center in China.MethodsIn this retrospective chart review, we evaluated 16 consecutive patients who received reduced-dose obinutuzumab (most commonly 1,000 mg for induction) after failure to achieve remission with cyclophosphamide (CTX) and/or rituximab (RTX) or who presented with severe, treatment-naïve disease. Primary endpoints were complete remission (CR) rates at 24 and 76 weeks. Secondary endpoints included changes in renal function, inflammatory biomarkers, and immune reconstitution. Adverse events were prospectively recorded.ResultsThe median age at obinutuzumab initiation was 44.5 years (IQR 31–54.3); 10 (62.5%) were men. The mean Birmingham Vasculitis Activity Score (BVAS) was 13.5 ± 6.4. There were 12 patients (75%) who had relapsing disease refractory to CTX/RTX, whereas four treatment-naïve patients presented with multiorgan failure. CR was achieved in 8/16 patients (50%) at week 24 and 13/16 patients (81.3%) at week 76. Obinutuzumab induced rapid clinical remission, suppressed systemic inflammation, achieved peripheral B-cell depletion, rendered ANCA-negative, and improved renal and pulmonary outcomes. No severe infections occurred. Seven patients (43.8%) developed treatment-emergent infections, predominantly respiratory (75%).ConclusionReduced-dose obinutuzumab demonstrates sustained remission in refractory or relapsing active AAV, achieving high long-term remission rates with an acceptable safety profile. No severe invasive infections were observed.